Empowerment for MsMEs jamu Cyrstal to Improve The Capability and Business Income of the Pondok Yatim Amal Bakti Foundation "Sudjono &Taruno" Jetis Village, Sukoharjo during the Covid-19 Pandemic - Syahri Alhusin; Laksono Sumarto; Mrih Rahayu (Community Development Journal, 2022)
The purpose of this service program is to increase the ability and income of students and foundation administrators through business assistance for Crystal herbal medicine. This community service activity was carried out from January to June 2021 at Pondok Yab Yatim Sudjono Taruno, Jetis Village, Baki District, Sukohardjo. The target of this activity is the students and dormitories of the Charity Bakti Foundation "Sudjono &Taruno" which operates 30 people. This activity is carried out using empowerment methods through training, counselling, and mentoring. The results of this service activity are: (1) the administrators and students have understood and mastered the basics of entrepreneurship and business methods well; (2) administrators and students are able to produce Crystal Jamu after practising training and education on herbal medicine-making; (3) administrators and students are able to market herbal products conventionally (offline) and online; (4) administrators and students know the process of obtaining a business license, as well as a BPOM permit. This service program also contributes to increasing the income of the crystal herbal medicine business at Pondok Yatim YAB Sudjono Taruno from Rp. 300,000 / month to Rp. 1,500,000 / month. The implementation of Community Service carried out by UTP FEB lecturers in producing Crystal Jamu has provided benefits for yab Sudjono &Taruno Yatim huts, both in order to improve health (body immunity) to prevent the spread of covid to students and administrators, congregations and the surrounding community, as well as being able to create useful business units to increase the management income of Pondok YAB Sudjono &Taruno